Phylogenetic relationships of geckos of the Hemiphyllodactylus harterti group, a new species from Penang Island, Peninsular Malaysia, and a likely case of true cryptic speciation - Cobos, Anthony; Grismer, L. Lee; Wood, Jr., Perry L.; Quah, Evan S. H.; Anuar, Shahrul; Muin, Mohd Abdul (Zootaxa, 2016)
An integrative taxonomic analysis based on the mitochondrial gene ND2 and its flanking tRNAs, morphology, and color pattern indicates that a newly discovered gecko described herein as Hemiphyllodactylus cicak sp. nov. from Penang Hill on the Island of Penang, Peninsular Malaysia is a member of the H. harterti group. Hemiphyllodactylus cicak sp. nov. is most closely related to the clade composed of the sister species H. harterti from Bukit Larut, Perak in the Bintang Mountain Range and H. bintik from Gunung Tebu, Terengganu from the Timur Mountain Range. These three allopatric species form a monophyletic group that extends approximately 270 km across three isolated mountain ranges in northern Peninsular Malaysia. The molecular analysis also indicates that H. titiwangsaensis from the Titiwangsa Mountain Range is composed of three genetically distinct allopatric populations. The southern two populations from Fraser’s Hill and Genting Highlands, Pahang have an uncorrected pairwise sequence divergence of 3.5% whereas these two populations have 12.4 and 12.8 % sequence divergences, respectively, from the northern population at Cameron Highlands, Pahang. Although the high sequence divergence clearly distinguishes the southern two populations from the former as a different species, all three populations are morphologically indistinguishable, leading to the hypothesis of a true, cryptic speciation event.